Megakaryocyte phenotyping in response to SARS-CoV-2 variants - Marcin A Sowa; Michael Tuen; Florencia Schlamp; Yuhe Xia; Marie I Samanovic; Mark J Mulligan; Tessa J Barrett (Platelets)
SARS-CoV-2 infection is associated with platelet hyperreactivity and increased rates of arterial and venous thrombosis. SARS-CoV-2 mutations have resulted in several variants with differences in transmissibility, infectivity, and patient outcomes. This study investigates the effects of the ancestral strain of SARS-CoV-2 (WA1) and two variants of concern, Delta and Omicron, on the human megakaryocyte (MK) phenotype and transcriptome. Human CD34+-derived MKs were incubated with WA1, Delta or Omicron SARS-CoV-2 variants for 24 hours. MK activation markers were measured under resting and thrombin-stimulated conditions. RNA-seq and cytokine release in response to the viruses were assessed. Plasma cytokines were measured in hospitalized COVID-19 patients. Treatment of MKs with WA1, Delta or Omicron variants of SARS-CoV-2 resulted in similar increases in classical activation markers. However, SARS-CoV-2 variants mediated distinct transcriptomic changes. Across variants, 60 genes overlapped, including CXCL8. Consistent with transcriptomic changes, SARS-CoV-2-incubated MKs secreted significantly elevated levels of IL-8. Among hospitalized COVID-19 patients, plasma IL-8 levels were highest in COVID-19 patients who subsequently experienced thrombotic events or died. In conclusion, WA1, Delta, and Omicron similarly induce classical MK activation responses while mediating distinct transcriptomic changes. Increased IL-8 levels may serve as a biomarker to inform platelet hyperreactivity and thrombotic events associated with COVID-19.